White supremacist performance and its refusal: a reflection on the mosque shootings in Christchurch, Aotearoa New Zealand. Issue 3 (2nd September 2021) - Willis, Emma
ABSTRACT: The terror attack carried out at two mosques in Aotearoa New Zealand by a white supremacist in 2019 was intended as a spectacle for mass public consumption. Its live-stream on Facebook invited hyper-identification (akin to a first-person shooter game), exploiting the disembodied nature of digital connection. In this essay, I draw from Judith Butler's concept of 'hallucinatory merging' to characterize this performativity and to suggest that both the killings and their filming were an attack on the 'generativity' of the assembly of bodies-in-prayer. The public response led by New Zealand's Prime Minister Jacinda Ardern avowedly rejected the ideology of white supremacy that motivated the attack. Her remark that 'this is not us' galvanized public sentiment, generating waves of public solidarity and a variety of public counter-performances. At the same time, this was a white supremacist act carried out in a settler (post-colonial) society, throwing into sharp relief the everyday performances of racial intolerance that trouble the notion that this is 'not us, ' a point made by various communities including Indigenous Māori. In tracing the two opposed modes of performance – that of white supremacist exclusivity and a national narrative of inclusion – I reflect on their entanglement as well as their distinction.